The Pullman Strike - O'Donnell, Edward T., 1963- author. Link
1 online resource.
Keywords: "This book examines the 1894 Pullman Strike, one of the most consequential clashes between labor and capital that paralyzed America's railroad system. The Pullman Strike is useful for all undergraduate students who study the Gilded Age, Industrial Relations, and labor, urban, and economic history in the United States"--